2008
DOI: 10.1051/medsci/2008242124
|View full text |Cite
|
Sign up to set email alerts
|

Les cellules gliales

Abstract: > La sclérose latérale amyotrophique (SLA) est la plus fréquente des affections des motoneurones, chez l'adulte. Elle se caractérise par une dégénérescence progressive des motoneurones entraînant une atrophie musculaire aboutissant à la mort des patients en moyenne 1 à 5 ans après le diagnostic. La plupart des cas de SLA sont sporadiques et 10 % sont des formes familiales. Les mutations les plus fréquemment rencontrées dans ces dernières sont dans le gène codant pour la superoxyde dismutase-1 (SOD1), une enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Neuroinflammation is a prominent feature of murine ALS animal models [1], [5], [9], [10], [11], [12], [44]. Despite strong evidence for microglial activation and release of pro-inflammatory cytokines driving disease progression, anti-inflammatory strategies have been overall disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is a prominent feature of murine ALS animal models [1], [5], [9], [10], [11], [12], [44]. Despite strong evidence for microglial activation and release of pro-inflammatory cytokines driving disease progression, anti-inflammatory strategies have been overall disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia substantially contribute to motor neuron death and disease progression in mSOD1 mouse models for ALS [4], [5], [6], [11], [14], [15]. Our study using the SOD1 G93A -model provides substantial in vivo evidence that microglia-mediated inflammation in the CNS comprises two different phases with fluent transition: i) in preclinical stages, microglia is highly reactive as indicated by an enhanced injury-induced response including rapid soma migration and early phagocytic activity; ii) in clinical stages, activated ameboid microglia lose their target-directed response, but instead show spontaneous activity as a gain of function and a loss of its role as highly dynamic surveillants of the CNS [19].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, microglia and astrocytes substantially contribute to motor neuron death and disease progression [4], [5], [6], [11], [12], [13], [14], [15]. In the case of microglia, selective silencing of the mutant gene in the innate immune cells of the CNS and in macrophages in a SOD1-model has substantially slowed disease progression [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…The glutamate release blocker Riluzole is, at present, the only authorized treatment for ALS; however, Riluzole treatment extends life expectancy by only a few months ( 3 ). It has been demonstrated that treatment with Riluzole for 12 months reduces deterioration of muscular function by 33.4% and extends life expectancy by 2.77 months ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, no treatments are able to prevent ALS progression. Riluzole is the only drug that is currently approved for the treatment of ALS and typically increases life expectancy by 3–6 months ( 3 7 ). Vitamin E is also often prescribed to patients with ALS due to its anti-oxidizing activity ( 8 ).…”
Section: Introductionmentioning
confidence: 99%